Natural products in attenuating renal inflammation via inhibiting the NLRP3 inflammasome in diabetic kidney disease - Wang, Yan; Sui, Zhun; Wang, Mi; Liu, Peng (Frontiers in Immunology, 2023)
Diabetic kidney disease (DKD) is a prevalent and severe complications of diabetes and serves as the primary cause of end-stage kidney disease (ESKD) globally. Increasing evidence indicates that renal inflammation is critical in the pathogenesis of DKD. The nucleotide - binding oligomerization domain (NOD) - like receptor family pyrin domain containing 3 (NLRP3) inflammasome is the most extensively researched inflammasome complex and is considered a crucial regulator in the pathogenesis of DKD. The activation of NLRP3 inflammasome is regulated by various signaling pathways, including NF- κB, thioredoxin—interacting protein (TXNIP), and non-coding RNAs (ncRNA), among others. Natural products are chemicals extracted from living organisms in nature, and they typically possess pharmacological and biological activities. They are invaluable sources for drug design and development. Research has demonstrated that many natural products can alleviate DKD by targeting the NLRP3 inflammasome. In this review, we highlight the role of the NLRP3 inflammasome in DKD, and the pathways by which natural products fight against DKD via inhibiting the NLRP3 inflammasome activation, so as to provide novel insights for the treatment of DKD.